Studi Tentang Penerapan Teknik Bertanya Probing Terhadap Kemampuan Komunikasi Matematis Siswa pada Pembelajaran Matematika di Kelas X.1 SMAN 1 Lubuk Sikaping - Maulana, Heru (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
The low result of mathematics learning outcomes of students in grade X.1 SMAN 1 Lubuk Si-kaping can be caused by the low ability of students mathematical communication. Generally, students is feeling difficult to express the ideas, solutions of a problem, whether it can be an answer or a re-sponse to what he or she thinks is poorly understood. One of the solution to solve this problem is by implementing probing technique which is a learning method by using questioning techniques that are digging knowledge of students. The purpose of this study is to describe the ability of students to com-municate the idea mathematically and to know the student learning outcomes during the application of probing techniques in learning mathematics grade X.1 SMAN 1 Lubuk Sikaping. This type of research is pre-experimented with The One-Shot Case Study design. The subject of this research is the students of grade X.1 SMAN 1 Lubuk Sikaping registered in second semester of academic year 2010/2011. Da-ta processing of students mathematical communication ability is by determining the percentage of the improvement of each indicator on observation sheet in every meeting and also supported by data from the interview. The results of this study illustrate that mathematical communication skills of students have increased from each meeting by using probing techniques, generally. As the results of learning mathematics after using the probing technique is good because 25 students (75.75%) of 33 students class X.1 SMAN 1 Lubuk Sikaping already reached Minimal Completeness Limit which has been ap-pointed by SMAN 1 Lubuk Sikaping (75).